Fuel-saving ship route using the Navy's ensemble meteorological and oceanic forecasts. (January 2015) - Chu, Peter C; Miller, Scott E; Hansen, James A
Fuel conservation and carbon reduction are important issues in current naval operations. Optimal ship route (i.e. minimum fuel consumption) depends on specific ship platform characteristics and near real-time environment such as weather, ocean waves, and ocean currents. The environmental impact of shipping can be measured on different spatial and temporal scales. As a vital component of the smart voyage planning (SVP) decision aid, the US Navy's meteorological and oceanographic (METOC) forecast systems play an important role in optimal ship routing, which enables fuel savings in addition to the aid of heavy weather avoidance. This study assesses the impact of METOC ensemble forecast systems on optimal ship route. Tests of the SVP decision aid tool are also conducted for operational fleet use and concept of operations for the USS Princeton guided missile cruiser (CG)-59 in a sea trial test following the 2012 Rim of the Pacific exercises.